Regulation and control method of dry-method electrode film coating process

By coating the dry electrode with conductive glue and using a water-based binder to form hydrogen bonds, the problem of insufficient adhesion between the dry film and the current collector caused by the PTFE binder is solved, and the cycle performance and conductivity of the battery are improved. .

CN119340346AActive Publication Date: 2025-01-21龙子湖新能源实验室 +1

Patent Information

Application Number
CN202411485733.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-21
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

In the dry electrode, the low surface energy of the PTFE adhesive leads to insufficient adhesion between the dry film and the current collector, which easily leads to peeling the dry film from the current collector, affecting the conductivity and cycling performance of the battery.

Method used

Before the collector and the dry membrane are compounded, coat the conductive glue, and use the carboxylic acid group in the hydrophilic binder to form a hydrogen bond with the collector and the dry membrane to enhance its adhesion.

Benefits of technology

By improving the adhesion of the dry membrane and collecting fluid, the cycle performance of the battery is enhanced, the internal resistance of the battery is reduced, and it is suitable for sensitive materials for water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340346A_ABST
    Figure CN119340346A_ABST
Patent Text Reader

Abstract

The invention discloses a regulation and control method of a dry-method electrode film coating process, which belongs to the technical field of batteries, and comprises the following steps: before compounding a current collector and a dry-method film, coating a conductive adhesive on the surface of the current collector, compounding the dry-method film with the current collector under the action of the conductive adhesive to obtain a dry-method pole piece, and the dry-method pole piece comprises the current collector, the conductive adhesive and the dry-method film. A water-based binder in the conductive adhesive contains a large number of carboxylic acid groups on the surface, and the carboxylic acid groups on the surface of the water-based binder form a large number of hydrogen bonds with the current collector and the dry-method film respectively, so that the binding power of the dry-method film and the current collector is increased. The process for preparing the conductive adhesive is simple and environment-friendly, no additional compound additive needs to be added, the conductive adhesive can be obtained only by mixing the water-based binder and the conductive material, and the prepared conductive adhesive is high in binding power. The conductive adhesive prepared by the invention selects a water-based binder, the surface of the conductive adhesive contains a large amount of carboxylic acid groups, and the carboxylic acid groups can respectively form hydrogen bonds with the surface of a current collector and a dry-process membrane to realize a bonding function, so that the bonding force of the dry-process membrane and the current collector is increased, the internal resistance is further reduced, and the rate capability and the cycle stability of the battery are improved. The dry-method electrode film coating process is simple to operate, low in cost, non-toxic and capable of realizing batch production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of batteries, and in particular relates to a control method for a dry electrode coating process. Background Art

[0002] In recent years, as Tesla, a leading electric car company, acquired Maxwell, a supercapacitor manufacturer, "dry electrode technology" has become a hot topic in the lithium battery industry. Compared with the traditional lithium battery wet process, the biggest feature of dry electrode technology is that it does not use any solvents, has outstanding advantages such as environmental friendliness, high energy density, good conductivity, and is more suitable for pre-lithiation technology and solid-state battery technology.

[0003] The dry electrode process is to dry-mix the active particles, conductive agent and then add the binder, form a self-supporting film under the fibrillation of the binder, and finally roll it to cover the surface of the current collector. No solvent is used in the production process of the dry electrode. The binder exists in the form of fibers and only has point contact with the surface of the active material particles, which does not affect the internal contact between the active material particles. The contact between the active material particles and the conductive agent particles is closer, and the conductivity of the electrode is good.

[0004] Binder is one of the important components of battery pole sheets. It is a polymer compound that adheres the active material and conductive agent in the electrode sheet to the electrode current collector. It has the function of enhancing the contact between the active material, conductive agent and current collector and stabilizing the pole sheet structure. It is an additional material with high technical content in battery materials. Studies have shown that although the amount of binder used in the electrode sheet is small, the quality of the binder performance directly affects the capacity, life and safety of the battery. Polymer binders achieve the integrity of electrode components by building a bridge between the current collector-conductive carbon black-active material. After the binder is adsorbed on the surface of the particles, a boundary layer, a solidified layer and a free layer are formed. Among them, the performance of the solidified layer and the free layer mainly depends on the bulk properties of the binder.

[0005] The binder used in the dry membrane in the dry electrode is PTFE, which is a polymer material with very unique properties. PTFE has extremely high resistance to almost all chemicals, including strong acids, strong bases and organic solvents, which makes it very popular in the chemical industry and laboratory equipment. PTFE has excellent mechanical properties and can remain stable at extreme temperatures. Its continuous use temperature range is usually between -200°C and 260°C, and its short-term temperature resistance can reach higher. However, PTFE has very low surface energy, which makes it non-sticky on most surfaces. This property is advantageous in some applications, but when used as an adhesive, the low surface energy may cause insufficient adhesion of PTFE to other materials, resulting in poor adhesion between the dry membrane and the current collector, which affects the overall resistance of the battery. The bonding strength of the dry membrane and the current collector is crucial. In the dry electrode, the binder in the dry membrane is PTFE, which makes the dry membrane easy to peel off from the current collector.

[0006] CN116487519A discloses a dry electrode, its preparation method and battery. The preparation method forms a uniform conductive glue by mixing a binder with a conductive material, and disperses the glue uniformly on the foil by adjusting the spraying aperture size, the distance between the nozzle and the foil, etc., so as to improve the peeling force of the dry electrode and reduce the impedance of the electrode sheet. However, the conductive glue used in the preparation method is in liquid state on the current collector, and wet coating is used. In order to avoid uneven coating due to its fluidity during wet coating, and the dry electrode film becomes wet during the compounding process, which is not conducive to rolling, resulting in problems such as sticking to the roller after winding and unstable rolling surface density, a dot diagram is used, and the area of ​​a single conductive glue does not exceed 1cm 2 , because the conductive glue is in the form of dots, the flow of the conductive glue on the foil is reduced. However, this method has the following problems: First, the binder used in the conductive glue is a water-based binder and an oil-based binder, and it is a wet dot pattern. The dry membrane selected is a sodium ion battery layered oxide positive electrode material, which is very sensitive to moisture. This limits the binder used in the conductive glue to only be the oil-based binder PVDF, and the oil-based binder PVDF has poor binding ability in the electrode. The mechanical properties of the PVDF binder used, the adhesion to the collector and the cohesion of the electrode membrane are not high, which limits the scope of application. Ternary materials and sulfide materials are sensitive to moisture and are also restricted. Second, the spray dot coating method is used to spray the conductive glue on the collector, which is not conducive to large-scale production. Third, the organic solvent used is volatile and has a certain toxicity, which increases the environmental protection cost. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a method for regulating a dry electrode coating process to improve the adhesion between the dry film and the current collector, improve the cycle performance of the battery, and reduce the internal resistance of the battery.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] A control method for a dry electrode coating process, characterized in that it comprises the following steps: before the current collector and the dry film are composited, a conductive adhesive is coated on the surface of the current collector, and the dry film is composited with the current collector through the action of the conductive adhesive to obtain a dry electrode sheet;

[0010] The aqueous binder in the conductive adhesive has a large number of carboxylic acid groups on its surface. The carboxylic acid groups on the surface of the aqueous binder form a large number of hydrogen bonds with the current collector and the dry film, thereby increasing the bonding force between the dry film and the current collector.

[0011] Furthermore, the dry electrode sheet includes a current collector, a conductive adhesive and a dry film;

[0012] The conductive adhesive is composed of a water-based binder I and a conductive agent;

[0013] The dry film is composed of active material, binder II and conductive agent.

[0014] Furthermore, the aqueous binder I in the conductive adhesive is an aqueous binder having a large number of carboxylic acid groups on the surface, including at least one of polyacrylic acid PAA, sodium carboxymethyl cellulose CMC / styrene-butadiene rubber SBR, and alginate ALG;

[0015] The conductive agent in the conductive adhesive includes any one of conductive carbon black, nano-carbon fiber, carbon nanotube, acetylene black, Ketjen black or graphene, or a combination of at least two of them.

[0016] Furthermore, the thickness of the dry film is 100-250 μm, and the composition of the dry film is: 95 wt% active material, 2 wt% binder II and 3 wt% conductive agent, wherein the active material includes one or a mixture of at least two of graphite, soft carbon, hard carbon, silicon-oxygen composite material, silicon-carbon composite material and ternary 811 material; the binder II is polytetrafluoroethylene PTFE or a combination of polytetrafluoroethylene PTFE and any one of polyvinylidene fluoride PVDF, polyacrylic acid PAA, polyethylene oxide PEO, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR. When PTFE is combined with other binders, the PTFE content is at least 50 wt%.

[0017] The conductive agent is any one of conductive carbon black, nano-carbon fiber, carbon nanotube, acetylene black, Ketjen black or graphene, or a combination of at least two of them.

[0018] The control method of the dry electrode coating process of the present invention specifically comprises the following steps:

[0019] (1) dissolving a certain amount of water-based binder in a water solvent and mixing the mixture uniformly to obtain a water-based binder solution;

[0020] (2) uniformly mixing a certain amount of aqueous binder solution and conductive agent to obtain a conductive adhesive;

[0021] (3) coating the conductive adhesive on the current collector using a flat coating machine, wherein the conductive adhesive coating thickness is 2 to 30 μm;

[0022] (4) After the conductive glue on the current collector evaporates, the dry film is coated on the current collector by heating and curing using a hot roller press and a flat plate hot pressing composite process.

[0023] Furthermore, the solid content of the aqueous binder in the aqueous binder solution of step (1) is 1-20 wt %.

[0024] Furthermore, in step (2), the mass ratio of the aqueous binder solution to the conductive agent is (70-98): (1-20).

[0025] Furthermore, in step (3), the coating thickness of the conductive glue on the current collector is 2 to 30 μm.

[0026] Furthermore, the current collector is a foil material, such as copper foil and carbon-coated copper foil.

[0027] Furthermore, the method for volatilizing the water content of the conductive glue on the current collector in step (4) is to naturally air-dry the current collector coated with the conductive glue in air for 5-9 hours, then bake it in a forced air oven at 40° C. for 6 hours, and then bake it at 80° C. for 1 hour.

[0028] Furthermore, the rolling temperature of the hot roller press described in step (4) is 100°C to 150°C, the roller gap distance of the roller press is adjusted to 80%-90% of the total thickness of the dry film thickness and the collector coated with conductive glue, the hot rolling speed is 0.5m / min to 3m / min; the flat plate hot pressing temperature is 100°C to 180°C, the pressure is 0.5T-2T, and the hot pressing time is 2-10s.

[0029] The beneficial effects of the present invention are as follows: the bonding strength between the dry film and the current collector is crucial. However, in the process of compounding the current collector and the dry film in the dry electrode, due to the presence of the PTFE binder, it has a very low surface energy and is not easy to bond, resulting in the dry film being easily peeled off from the current collector. In the present invention, before compounding the current collector and the dry film, a conductive adhesive is coated on the surface of the current collector. After the conductive adhesive on the surface of the current collector is dried, the dry film is compounded with the current collector through the action of the conductive adhesive to obtain a dry electrode. The surface of the aqueous binder in the selected conductive adhesive contains a large number of carboxylic acid groups. The surface carboxylic acid groups form a large number of hydrogen bonds with the current collector and the dry film, thereby increasing the bonding force between the dry film and the current collector. Secondly, the conductive glue used in the present invention is solid on the current collector, and a dry coating is used. The adhesive in the conductive glue forms hydrogen bonds with the current collector and the dry film under high-temperature rolling and hot pressing to increase the bonding force. The method used in the present invention not only has better bonding force than the oil-based adhesive, but also has a wider range of applications, and is suitable for water-sensitive materials such as ternary positive electrodes, lithium titanate negative electrodes, solid sulfides and sodium electric materials. The dry electrode coating process of the present invention is simple to operate, low in cost, non-toxic, and can be produced in batches. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is the effect of the drying method on the conductive adhesive coating current collector in comparative example 1.

[0032] Figure 2 The effect of the drying method in Example 1 on the coating effect of the conductive adhesive on the current collector is shown in FIG. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below by specific implementation methods. It should be clear to those skilled in the art that the embodiments are only to help understand the present invention and should not be a specific limitation of the present invention.

[0034] The dry electrode described in the present invention comprises a current collector, a conductive glue and a dry film.

[0035] According to the technical solution of the present invention, a method for regulating a dry electrode coating process is provided to increase the adhesion between the dry film and the current collector, improve the cycle performance of the battery, and reduce the internal resistance of the battery.

[0036] Example 1

[0037] The present embodiment provides a control method for a dry electrode coating process, and the steps are as follows:

[0038] (1) Preparation of conductive adhesive: A certain amount of PAA and water were mixed uniformly in a degassing machine according to the following parameters: first, the mixture was rotated at a low speed of 600 rpm, 900 rpm and 1200 rpm for 300 s, 360 s and 180 s respectively, then kept still for 300 s, and then rotated at a high speed of 1200 rpm, 1500 rpm and 1800 rpm for 300 s, 360 s and 180 s respectively, to obtain a PAA aqueous adhesive solution with a solid content of 5 wt%.

[0039] (2) A PAA aqueous binder solution and an SP conductive agent with a mass ratio of 95:5 were placed in a degassing machine and mixed according to the following parameters: first, they were rotated at low speeds of 300 rpm, 600 rpm and 900 rpm for 120 s, 150 s and 120 s, respectively, and then stopped for 300 s; then, they were rotated at medium speeds of 600 rpm, 900 rpm and 1200 rpm for 300 s, 360 s and 180 s, respectively, and then stopped for 300 s; finally, they were rotated at high speeds of 1500 rpm, 1800 rpm and 2600 rpm for 300 s, 600 s and 180 s, respectively, to obtain a conductive adhesive.

[0040] (3) Use a flat plate coating machine to coat the conductive adhesive on the copper foil current collector. The conductive adhesive coating thickness is 5 μm and the coating speed is 3 cm / s. The current collector coated with the conductive adhesive is naturally air-dried in the air for 5 hours, then placed in a forced air oven at 40°C for 6 hours, and then baked at 80°C for 1 hour.

[0041] (4) A graphite dry film is coated on a copper foil current collector coated with a conductive adhesive, the gap distance of a roller press is adjusted to be 80% of the thickness of the current collector coated with the conductive adhesive plus the total thickness of the dry film, the hot rolling speed is 0.5 m / min, the hot rolling temperature of the hot rolling machine is 110°C, and a graphite dry film with a thickness of 150 μm is coated on the copper foil current collector to preliminarily obtain a graphite dry electrode; the graphite dry film is composed of 95 wt% graphite, 2 wt% binder PTFE, and 3 wt% conductive carbon black.

[0042] (5) The graphite dry-process electrode in step (4) is further coated by using a flat hot press, and the hot pressing temperature is set to 130° C., the pressure is 1T, and the hot pressing time is set to 5 s to obtain a graphite dry-process electrode.

[0043] Example 2

[0044] The present embodiment provides a control method for a dry electrode coating process, and the steps are as follows:

[0045] (1) Preparation of conductive adhesive: A certain amount of PAA and water were mixed uniformly in a degassing machine according to the following parameters: first, the mixture was rotated at a low speed of 400 rpm, 600 rpm and 900 rpm for 300 s, 360 s and 180 s respectively, then left to stand for 300 s, and then rotated at a high speed of 900 rpm, 1200 rpm and 1500 rpm for 300 s, 360 s and 180 s respectively, to obtain a PAA aqueous adhesive solution with a solid content of 1%.

[0046] (2) A PAA aqueous binder solution and an SP conductive agent with a mass ratio of 80:1 were placed in a degassing machine and mixed according to the following parameters: first, they were rotated at low speeds of 300 rpm, 600 rpm and 900 rpm for 120 s, 150 s and 120 s, respectively, and then stopped for 300 s; then, they were rotated at medium speeds of 600 rpm, 900 rpm and 1200 rpm for 300 s, 360 s and 180 s, respectively, and then stopped for 300 s; finally, they were rotated at high speeds of 1500 rpm, 1800 rpm and 2600 rpm for 300 s, 600 s and 180 s, respectively, to obtain a conductive adhesive.

[0047] (3) Use a flat plate coating machine to coat the conductive adhesive on the copper foil current collector. The conductive adhesive coating thickness is 2 μm and the coating speed is 1 cm / s. The current collector coated with the conductive adhesive is naturally air-dried in the air for 6 hours, then placed in a forced air oven at 40°C for 6 hours, and then baked at 80°C for 1 hour.

[0048] (4) A silicon-carbon dry film is coated on a copper foil current collector coated with a conductive adhesive, and the roller gap distance of the roller press is adjusted to 85% of the thickness of the dry film plus the thickness of the current collector coated with the conductive adhesive. The hot rolling speed is 1 m / min, and the hot rolling temperature of the hot rolling machine is 130°C. A silicon-carbon composite material with a thickness of 180 μm is dry-coated on the copper foil current collector. The silicon-carbon composite material dry film composition is 95 wt% silicon-carbon composite material, 2 wt% binder PTFE, 2 wt% conductive carbon black + 1 wt% carbon nanotubes, and a silicon-carbon composite material dry electrode is preliminarily obtained.

[0049] (5) The silicon-carbon composite material dry-process electrode in step (4) is further coated with a flat hot press, and the hot pressing temperature is set to 150°C, the pressure is 0.5T, and the hot pressing time is 10s to obtain a silicon-carbon composite material dry-process electrode.

[0050] Example 3

[0051] The present embodiment provides a control method for a dry electrode coating process, and the steps are as follows:

[0052] (1) Preparation of conductive adhesive: A certain amount of ALG and water were mixed uniformly in a degassing machine according to the following parameters: first, the mixture was rotated at a low speed of 200 rpm, 600 rpm and 800 rpm for 600 s, 300 s and 180 s respectively, then kept still for 300 s, and then rotated at a high speed of 600 rpm, 900 rpm and 1200 rpm for 600 s, 300 s and 180 s respectively, to obtain an ALG aqueous adhesive solution with a solid content of 10 wt%.

[0053] (2) A PAA aqueous binder solution and an acetylene black conductive agent with a mass ratio of 75:5 were placed in a degassing machine and mixed according to the following parameters: first, they were rotated at low speeds of 200 rpm, 600 rpm and 800 rpm for 300 s, 150 s and 120 s, respectively, and then stopped for 300 s; then, they were rotated at medium speeds of 600 rpm, 900 rpm and 1200 rpm for 600 s, 300 s and 180 s, respectively, and then stopped for 300 s; finally, they were rotated at high speeds of 1500 rpm, 1800 rpm and 2600 rpm for 300 s, 600 s and 180 s, respectively, to obtain a conductive adhesive.

[0054] (3) Use a flat plate coating machine to coat the conductive adhesive on the copper foil current collector. The conductive adhesive coating thickness is 10 μm and the coating speed is 2 cm / s. The current collector coated with the conductive adhesive is naturally air-dried in the air for 8 hours, then placed in a forced air oven at 40°C for 6 hours, and then baked at 80°C for 1 hour.

[0055] (4) A silicon-oxygen dry film is coated on a copper foil current collector coated with a conductive adhesive, and the roller gap distance of the roller press is adjusted to be 90% of the total thickness of the dry film thickness plus the current collector coated with the conductive adhesive. The hot rolling speed is 3 m / min, and the hot rolling temperature of the hot rolling machine is 150°C. A silicon-oxygen composite material with a thickness of 200 μm is dry-coated on the copper foil current collector. The silicon-oxygen composite material dry film composition is 95 wt% silicon-oxygen composite material, 1.5 wt% binder PTFE+0.5 wt% PAA, 2 wt% conductive carbon black+1 wt% carbon nanotubes, and a silicon-oxygen composite material dry electrode is preliminarily obtained.

[0056] (5) The silicon-oxygen composite material dry-process electrode in step (4) is further coated with a flat hot press, and the hot pressing temperature, pressure and time are set to 140° C., 2T and 2s, to obtain a silicon-oxygen composite material dry-process electrode.

[0057] Example 4

[0058] The present embodiment provides a control method for a dry electrode coating process, and the steps are as follows:

[0059] (1) Preparation of conductive adhesive: A certain amount of CMC / SBR (mass ratio 1:1) and water were mixed uniformly in a degassing machine according to the following parameters: first, the mixture was rotated at a low speed of 150 rpm, 300 rpm and 400 rpm for 600 s, 120 s and 180 s respectively, then left to stand for 300 s, and then rotated at a high speed of 200 rpm, 400 rpm and 1200 rpm for 600 s, 120 s and 180 s respectively, to obtain a CMC / SBR aqueous binder solution with a solid content of 20%.

[0060] (2) A PAA aqueous binder solution and a nano-carbon fiber conductive agent with a mass ratio of 80:20 were placed in a degassing machine and mixed according to the following parameters: first, they were rotated at a low speed of 150 rpm, 300 rpm and 400 rpm for 600 s, 120 s and 180 s respectively, and then stopped for 300 s; then, they were rotated at a medium speed of 200 rpm, 400 rpm and 500 rpm for 600 s, 120 s and 180 s respectively, and then stopped for 300 s; finally, they were rotated at a high speed of 300 rpm, 500 rpm and 800 rpm for 300 s, 180 s and 120 s respectively to obtain a conductive adhesive.

[0061] (3) Use a flat plate coating machine to coat the conductive glue on the current collector. The conductive glue coating thickness is 25 μm and the coating speed is 2 cm / s. The current collector coated with the conductive glue is naturally air-dried in the air for 9 hours, and then placed in a forced air oven at 40°C for 6 hours, and then baked at 80°C for 1 hour.

[0062] (4) A graphite dry film is coated on a copper foil current collector coated with a conductive adhesive, the gap distance of the roller press is adjusted to 86% of the total thickness of the dry film thickness plus the current collector coated with the conductive adhesive, the hot rolling speed is 1.5 m / min, the hot rolling temperature of the hot rolling machine is 120°C, and a graphite material with a thickness of 220 μm is dry-coated on the copper foil current collector. The graphite dry film composition is 95 wt% graphite, 1.5 wt% binder PTFE + 0.5 wt% PAA, 2 wt% conductive carbon black + 1 wt% carbon nanotubes, and a graphite dry electrode is preliminarily obtained.

[0063] (5) The graphite dry-process electrode in step (4) is further coated by using a flat hot press, and the hot pressing temperature is set to 180° C., the pressure is set to 0.6 T, and the hot pressing time is set to 10 s to obtain a graphite dry-process electrode.

[0064] Example 5

[0065] The present embodiment provides a control method for a dry electrode coating process, and the steps are as follows:

[0066] (1) Preparation of conductive adhesive: A certain amount of PAA and water were mixed uniformly in a degassing machine according to the following parameters: first, the mixture was rotated at a low speed of 600 rpm, 900 rpm and 1200 rpm for 300 s, 360 s and 180 s respectively, then kept still for 300 s, and then rotated at a high speed of 1200 rpm, 1500 rpm and 1800 rpm for 300 s, 360 s and 180 s respectively, to obtain a PAA aqueous adhesive solution with a solid content of 7 wt %.

[0067] (2) A PAA aqueous binder solution and an SP conductive agent with a mass ratio of 96:3 were placed in a degassing machine and mixed according to the following parameters: first, they were rotated at low speeds of 300 rpm, 600 rpm and 900 rpm for 120 s, 150 s and 120 s, respectively, and then stopped for 300 s; then, they were rotated at medium speeds of 600 rpm, 900 rpm and 1200 rpm for 300 s, 360 s and 180 s, respectively, and then stopped for 300 s; finally, they were rotated at high speeds of 1500 rpm, 1800 rpm and 2600 rpm for 300 s, 600 s and 180 s, respectively, to obtain a conductive adhesive.

[0068] (3) Use a flat plate coating machine to coat the conductive adhesive on the aluminum foil current collector. The conductive adhesive coating thickness is 10 μm and the coating speed is 3 cm / s. The current collector coated with the conductive adhesive is naturally air-dried in the air for 6 hours, then placed in a forced air oven at 40°C for 6 hours, and then baked at 80°C for 1 hour.

[0069] (4) A graphite dry film is coated on an aluminum foil current collector coated with a conductive adhesive, the roller gap distance of the roller press is adjusted to be 90% of the thickness of the current collector coated with the conductive adhesive plus the total thickness of the dry film, the hot rolling speed is 0.5 m / min, the hot rolling temperature of the hot rolling machine is 130°C, and a ternary 811 with a thickness of 150 μm is dry coated on the aluminum foil current collector to preliminarily obtain a ternary 811 dry electrode; the ternary 811 dry film composition is 95wt% ternary 811, 2wt% binder PTFE, 1wt% conductive carbon black + 2wt% carbon nanotubes.

[0070] (5) The ternary 811 dry-process electrode in step (4) is further coated with a flat hot press, and the hot pressing temperature, pressure and time are set to 130°C, 1T and 5s, to obtain a ternary 811 dry-process electrode.

[0071] Comparative Example 1

[0072] This comparative example provides a control method for a dry electrode coating process, wherein after a conductive adhesive is coated on a current collector using a flat-plate coating machine, the current collector coated with the conductive adhesive is not naturally air-dried in the air, but is directly placed in a forced air oven at 40° C. for 6 hours, and then at 80° C. for 1 hour. In addition, the other conditions are exactly the same as those in Example 1.

[0073] Comparative Example 2

[0074] This comparative example provides a control method for a dry electrode coating process, in which the conductive adhesive in the method does not use a carboxylic acid-containing binder, but uses PI (polyimide) as a binder, and the corresponding solvent uses DMF (N,N-dimethylformamide). In addition, the other conditions are exactly the same as those in Example 1.

[0075] Comparative Example 3

[0076] This comparative example provides a control method for a dry electrode coating process, in which the conductive adhesive in the method does not use a carboxylic acid-containing binder, but uses PVDF (polyvinylidene fluoride) as a binder, and the corresponding solvent uses NMP (N-methylpyrrolidone). In addition, the other conditions are exactly the same as those in Example 1.

[0077] Comparative Example 4

[0078] This comparative example provides a control method for a dry electrode coating process, in which the conductive adhesive in the method does not use a carboxylic acid-containing binder, but uses PVP (polyvinyl pyrrolidone) as a binder, and the corresponding solvent is water. In addition, the other conditions are exactly the same as those in Example 1.

[0079] Comparative Example 5

[0080] This comparative example provides a method for regulating a dry electrode coating process, wherein the SP content of the conductive adhesive in the method is 0. In addition, the other conditions are exactly the same as those in Example 1.

[0081] Comparative Example 6

[0082] This comparative example provides a control method for a dry electrode coating process, wherein the hot roller pressing temperature of the method is 80° C. In addition, the other conditions are exactly the same as those in Example 1.

[0083] Comparative Example 7

[0084] This comparative example provides a wet electrode having the same ratio of active material: binder: conductive agent as that in the dry membrane. In Example 1, the dry electrode has graphite: PTFE: conductive agent = 95:2:3, and the wet electrode has graphite: CMC: SBR: conductive agent = 95:1:1:3, which are coated on copper foil with a 150μm scraper.

[0085] Performance Testing

[0086] The adhesion between the membrane and the current collector and the impedance test results in each embodiment and comparative example are shown in Table 1.

[0087] Table 1 shows the adhesion and impedance test results of the embodiments and comparative examples.

[0088] Group Adhesion force(N) <![CDATA[Impedance (Ωcm -2 )]]> Example 1 0.37 0.02201 Example 2 0.36 0.02698 Example 3 0.38 0.03046 Example 4 0.35 0.03215 Example 5 0.36 0.02886 Comparative Example 1 / / Comparative Example 2 0.13 0.19687 Comparative Example 3 0.15 0.13717 Comparative Example 4 0.12 0.26187 Comparative Example 5 0.38 2.32153 Comparative Example 6 0.03 0.03537 Comparative Example 7 0.14 0.47591

[0089] The dry-process electrodes and wet-process electrodes of each embodiment and comparative example were assembled into a button battery, and the initial efficiency, 0.2C initial discharge specific capacity, 50-cycle and 100-cycle specific capacity retention rates were tested. The test results are shown in Figure 2.

[0090] Table 2 Electrochemical performance test results of the embodiments and comparative examples

[0091]

[0092] The results in Table 1 and Table 2 show that the dry electrode prepared by the method of the present invention has greater bonding force, smaller impedance and excellent electrochemical performance.

[0093] Through Examples 1-4 and Comparative Example 7 in Table 1, it is found that the bonding force between the active material and the current collector of the dry-process electrode of the present invention is stronger than that of the wet-process electrode. At the same time, through impedance testing, the impedance between the active material and the current collector in the dry-process electrode of the present invention is also smaller than that of the wet-process electrode. Through the electrochemical performance comparison of Examples 1-4 and Comparative Example 7 in Table 2, its performance is comparable to that of the wet-process electrode. However, the dry-process electrode has an absolute advantage over the wet-process electrode in terms of preparation process and cost.

[0094] Example 5 is a ternary positive electrode 811 material, which is sensitive to moisture. Since the conductive glue on the current collector has been removed during the coating process of this patent, the prepared ternary positive electrode 811 electrode has excellent performance, indicating that the coating process of the present invention is applicable to a wide range of fields.

[0095] In the method described in Comparative Example 2-4, when the dry film and the current collector are composited with an oily adhesive or an aqueous adhesive without a carboxylic acid group as the binder in the conductive adhesive, the bonding strength value decreases and the impedance increases, which is predicted to affect the cycle life. Judging from the capacity retention rate of 50 and 100 cycles, the cycle performance of Comparative Example 2-4 is poor, which is consistent with the poor bonding strength and high impedance of Comparative Example 2-4 in Table 1.

[0096] The conductive adhesive in the method described in Comparative Example 5 has an SP content of 0, and the dry film is connected to the current collector through a PAA adhesive. The interface impedance is too large, and there is no need to assemble and test the electrochemical performance.

[0097] The rolling temperature of the hot roller press in the method described in Comparative Example 6 is 80°C. The temperature is too low during coating, which is not conducive to the formation of hydrogen bonds between the binder in the conductive adhesive and the dry film and the current collector, resulting in low bonding strength with the current collector, thereby affecting the coating effect and other electrochemical properties.

[0098] Figure 1For comparative example 1, after the conductive glue is coated on the current collector with a flat coating machine, the current collector coated with the conductive glue is not naturally air-dried in the air, but is directly placed in a forced air oven at 40°C for 6 hours, and then at 80°C for 1 hour. It is found that the conductive glue is intact during air drying and in the oven, but when it is taken out of the oven, the conductive glue begins to break. In the same way, the foil coated with the conductive glue is air-dried in the air for 1 hour, as described in Example 1, and then placed in an oven at 40°C for 6 hours, and then at 80°C for 1 hour. The conductive glue does not break, as shown in the picture. Figure 2 shown.

[0099] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A control method for a dry electrode coating process, characterized in that: The following steps are involved: Before the current collector and the dry film are combined, a conductive adhesive is coated on the surface of the current collector, and the dry film is combined with the current collector through the action of the conductive adhesive to obtain a dry electrode; The aqueous binder in the conductive adhesive has a large number of carboxylic acid groups on its surface. The carboxylic acid groups on the surface of the aqueous binder form a large number of hydrogen bonds with the current collector and the dry film, thereby increasing the bonding force between the dry film and the current collector.

2. The control method of the dry electrode coating process according to claim 1, characterized in that: The dry-process electrode sheet comprises a current collector, a conductive adhesive and a dry-process film; The conductive adhesive is composed of a water-based binder I and a conductive agent; The dry film is composed of active material, binder II and conductive agent.

3. The control method of the dry electrode coating process according to claim 2, characterized in that: The aqueous binder I in the conductive adhesive is an aqueous binder having a large number of carboxylic acid groups on the surface, including at least one of polyacrylic acid PAA, sodium carboxymethyl cellulose CMC / styrene-butadiene rubber SBR, and alginate ALG; The conductive agent in the conductive adhesive includes any one of conductive carbon black, nano-carbon fiber, carbon nanotube, acetylene black, Ketjen black or graphene, or a combination of at least two of them.

4. The control method of the dry electrode coating process according to claim 2, characterized in that: The dry film has a thickness of 100-250 μm, and the composition of the dry film is: 95 wt% of active material, 2 wt% of binder II and 3 wt% of conductive agent, wherein the active material includes one or a mixture of at least two of graphite, soft carbon, hard carbon, silicon-oxygen composite material, silicon-carbon composite material and ternary 811 material; The binder II is polytetrafluoroethylene (PTFE) or a combination of polytetrafluoroethylene (PTFE) and any one of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polyethylene oxide (PEO), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR). When PTFE is combined with other binders, the PTFE content is at least 50wt%; The conductive agent is any one of conductive carbon black, nano-carbon fiber, carbon nanotube, acetylene black, Ketjen black or graphene, or a combination of at least two of them.

5. The control method of the dry electrode coating process according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) dissolving a certain amount of water-based binder in a water solvent and mixing them evenly to obtain a water-based binder solution; (2) uniformly mixing a certain amount of aqueous binder solution and conductive agent to obtain a conductive adhesive; (3) Coating the conductive adhesive on the current collector using a flat coating machine, with the conductive adhesive coating thickness ranging from 2 to 30 μm; (4) After the conductive glue on the current collector evaporates, the dry film is coated on the current collector by heating and curing using a hot roller press and a flat plate hot pressing composite process.

6. The control method of the dry electrode coating process according to claim 5, characterized in that: The solid content of the aqueous binder in the aqueous binder solution of step (1) is 1-20wt%.

7. The control method of the dry electrode coating process according to claim 5, characterized in that: The mass ratio of the aqueous binder solution to the conductive agent in step (2) is (70-98):(1-20).

8. The control method of the dry electrode coating process according to claim 5, characterized in that: In step (3), the conductive adhesive is coated on the current collector to a thickness of 2 to 30 μm.

9. The control method of the dry electrode coating process according to claim 5, characterized in that: The method for volatilizing the water content of the conductive glue on the current collector in step (4) is to naturally air-dry the current collector coated with the conductive glue in air for 5-9 hours, then bake it in a forced air oven at 40°C for 6 hours, and then bake it at 80°C for 1 hour.

10. The control method of the dry electrode coating process according to claim 5, characterized in that: The hot roller pressing temperature of step (4) is 100°C to 150°C, the roller gap distance of the roller pressing machine is adjusted to 80%-90% of the total thickness of the dry film thickness and the current collector coated with conductive glue, the hot roller rolling speed is 0.5m / min to 3m / min; the flat plate hot pressing temperature is 100°C to 180°C, the pressure is 0.5T-2T, and the hot pressing time is 2-10s.

Citation Information

Patent Citations

  • Hybrid energy storage device lithium-containing metal negative electrode preparation method

    CN108346523A

  • Preparation method and application of dry electrode based on polymer current collector

    CN116014061A

  • Pole piece and battery

    CN116315169A

  • Dry-method electrode, preparation method thereof and battery

    CN116487519A

  • Primer for dry-method electrode and preparation method thereof, composite current collector, battery pole piece, secondary battery, battery module, battery pack and electric device

    CN118120072A

Cited By

  • High-adhesion positive pole piece for solid-state lithium battery and preparation method of high-adhesion positive pole piece

    CN121260731A